2013
DOI: 10.1016/j.jsb.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of DDR1 ECD affects receptor–ligand binding

Abstract: Discoidin Domain Receptor 1 (DDR1) is a widely expressed receptor tyrosine kinase (RTK) which regulates cell differentiation, proliferation and migration and remodeling of the extracellular matrix. Collagen(s) are the only known ligand for DDR1. We have previously reported that collagen stimulation leads to oligomerization of the full length receptor. In this study we investigated the effect of oligomerization of the DDR1 extracellular domain (ECD) pre and post ligand binding. Solid phase binding assays showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Recent work using cells expressing DDR1d, a kinase-deficient isoform, supports the involvement of the kinase domain in regulating receptor oligomerization, auto-phosphorylation and clustering at the cell surface [118]. We found that upon fibrillar collagen stimulation, activated DDR1 (phosphorylation at the kinase domain (Y792)) was mainly present as oligomers, which supports the notion that receptor oligomerization precedes receptor activation [13,117]. Cells expressing the kinase-depleted DDR1d and cells expressing a kinase-dead DDR1 isoform (DDR1e) formed clusters but cells that express kinase-active DDR1 (DDR1b) exhibited large increases in cluster size.…”
Section: A Ddr1 Activation: a Central Regulator Of Collagen And Myossupporting
confidence: 84%
See 1 more Smart Citation
“…Recent work using cells expressing DDR1d, a kinase-deficient isoform, supports the involvement of the kinase domain in regulating receptor oligomerization, auto-phosphorylation and clustering at the cell surface [118]. We found that upon fibrillar collagen stimulation, activated DDR1 (phosphorylation at the kinase domain (Y792)) was mainly present as oligomers, which supports the notion that receptor oligomerization precedes receptor activation [13,117]. Cells expressing the kinase-depleted DDR1d and cells expressing a kinase-dead DDR1 isoform (DDR1e) formed clusters but cells that express kinase-active DDR1 (DDR1b) exhibited large increases in cluster size.…”
Section: A Ddr1 Activation: a Central Regulator Of Collagen And Myossupporting
confidence: 84%
“…One proposed mechanism for activation involves collagen-induced DDR1 clustering [114,116] since DDR1 oligomerization is required for high affinity binding to collagen [117]. Recent work using cells expressing DDR1d, a kinase-deficient isoform, supports the involvement of the kinase domain in regulating receptor oligomerization, auto-phosphorylation and clustering at the cell surface [118].…”
Section: A Ddr1 Activation: a Central Regulator Of Collagen And Myosmentioning
confidence: 99%
“…Work using cells expressing DDR1d, a kinase-deficient isoform, supports the involvement of the kinase domain in regulating receptor oligomerization, auto-phosphorylation, and clustering at the cell surface (Fu et al, 2014). We found that in cells binding to fibrillar collagen, activated DDR1 was mainly oligomeric, supporting the notion that receptor oligomerization precedes receptor activation (Yeung et al, 2013). Furthermore, we found that cells expressing the kinase-depleted DDR1 (DDR1d), cells expressing kinase-dead DDR1 (DDR1e), or DDR1 OE cells cultured on non-activating fibronectin substrates all formed clusters.…”
supporting
confidence: 72%
“…WT OE W W W WT WT WT WT W WT WT WT W WT W WT W WT W W WT WT WT WT WT WT T WT T T WT WT WT W WT W W WT W WT WT W W W W W WT WT W WT WT WT T T T WT WT WT WT WT W WT W W W WT WT W W W WT T T T W WT WT WT T WT T T W W W WT W W WT T WT T T T W W WT T high-affinity binding to collagen (Yeung et al, 2013). Work using cells expressing DDR1d, a kinase-deficient isoform, supports the involvement of the kinase domain in regulating receptor oligomerization, auto-phosphorylation, and clustering at the cell surface (Fu et al, 2014).…”
mentioning
confidence: 99%
“…Unlike most RTKs that undergo dimerization upon ligand binding, DDRs appear to exist in dimers prior to interaction with the ligand (Abdulhussein et al, 2008;Mihai et al, 2009;Noordeen et al, 2006). Studies from Agarwal et al (2007) and Leitinger (2003) showed that DDR dimerization was a prerequisite for high affinity binding to collagen, and DDR oligomerization greatly enhanced their affinity to collagen (Agarwal et al, 2007;Mihai et al, 2006;Yeung et al, 2013). Collagen interacts with pre-formed DDR dimers and upon binding induces dimer oligomerization, conformational changes and autophosphorylation on multiple tyrosine residues within cytosolic JM and kinase domain of DDRs, and thus results in receptor activation.…”
Section: Ddrs Structure and Activationmentioning
confidence: 99%